About Professional Selection Criteria And The Career Guidance Of Future Resuscitators With The Fact Of The Phenomenon Of Burnout - Ivanova Polina Pavlovna; Semikova Anastasia Pavlovna; Grigoryan Liana Artakovna; Vysharenko Leila Shamilevna; Khrol Vsevolod Igorevich; Vershinina Daria Sergeevna (Journal for ReAttach Therapy and Developmental Diversities, 2024)
Introduction. The selection criteria for medical activities are based on the study of the applicant`s level of professional training, a psychological portrait, and the exclusion of chronic pathology. They are not enough to predict the adaptation of an employee to a profession. About the serious defects in the organization of personnel selection and support are evidenced by the spread of professional burnout syndrome (PBS) [2].